Use of Fondaparinux Following Elective Lumbar Spine Surgery Is Associated With a Reduction in Symptomatic Venous Thromboembolism. Issue 7 (October 2020) - Fourman, Mitchell S.; Shaw, Jeremy D.; Nwasike, Chinedu O.; Boakye, Lorraine A. T.; Dombrowski, Malcolm E.; Vaudreuil, Nicholas J.; Wawrose, Richard A.; Lunardini, David J.; Lee, Joon Y.
Study Design: Retrospective cohort study. Objective: To assess the impact of fondaparinux on venous thromboembolism (VTE) following elective lumbar spine surgery in high-risk patients. Methods: Matched patient cohorts who did or did not receive inpatient fondaparinux starting postoperative day 2 following elective lumbar spine surgery were compared. All patients received 1 month of acetyl salicylic acid 325 mg following discharge. The primary outcome was a symptomatic DVT (deep vein thrombosis) or PE (pulmonary embolus) within 30 days of surgery. Secondary outcomes included prolonged wound drainage, epidural hematoma, and transfusion. Results: A significantly higher number of DVTs were diagnosed in the group that did not receive inpatient VTE prophylaxis (3/102, 2.9%) compared with the fondaparinux group (0/275, 0%, P = .02). Increased wound drainage was seen in 18.5% of patients administered fondaparinux, compared with 25.5% of untreated patients ( P = .15). Deep infections were equivalent (2.2% with fondaparinux vs 4.9% control, P = .18). No epidural hematomas were noted, and the number of transfusions after postoperative day 2 and 90-day return to operating room rates were equivalent. Conclusions: Patients receiving fondaparinux had lower rates of symptomatic DVT and PE and a favorable complication profile when compared with matched controls. The retrospective nature of this work limits the safety and efficacy claims that can be made about the use of fondaparinux to prevent VTE in elective lumbar spine surgery patients. Importantly, this work highlights the potential safety of this regimen, permitting future high-quality trials.